Innate immunity of vascular smooth muscle cells contributes to two-wave inflammation in atherosclerosis, twin-peak inflammation in aortic aneurysms and trans-differentiation potential into 25 cell types - Yang, Qiaoxi; Saaoud, Fatma; Lu, Yifan; Pu, Yujiang; Xu, Keman; Shao, Ying; Jiang, Xiaohua; Wu, Sheng; Yang, Ling; Tian, Ying; Liu, Xiaolei; Gillespie, Avrum; et al. (Frontiers in Immunology, 2024)
To determine the roles of innate immunity in vascular smooth muscle cell (VSMC) and aortic pathologies, we performed transcriptome analyses on aortas from ApoE–/– angiotensin-II (Ang-II)-induced aortic aneurysm (AAA) time course, and ApoE–/– atherosclerosis time course, as well as VSMCs stimulated with danger-associated molecular patterns (DAMPs), and made significant findings: 1) the upregulated innate immune pathways (UIIPs) in ApoE–/– Ang-II-induced AAA at 7 days were different from that of 14 and 28 days; and AAA showed twin-peaks of UIIPs with a major peak at 7 days and a minor peak at 28 days; 2) all the UIIPs in ApoE–/– atherosclerosis at 6 weeks were different from that of 32 and 78 weeks (two waves); 3) analyses of additional 12 lists of innate immune-related genes with 1325 cytokine/chemokine genes, 2202 plasma membrane protein genes, 373 clusters of differentiation (CD) marker genes, 280 nuclear membrane protein genes, 1425 nucleoli protein genes, 6750 nucleoplasm protein genes, 1496 transcription factors (TFs) including 15 pioneer TFs, 164 histone modification enzymes, 102 oxidative cell death genes, 68 necrotic cell death genes, and 47 efferocytosis genes confirmed two-wave inflammation in atherosclerosis and twin-peak inflammation in AAA; 4) DAMPs-stimulated VSMCs were innate immune cells as judged by the upregulation of innate immune genes and genes from 12 additional lists; 5) DAMPs-stimulated VSMCs increased trans-differentiation potential by upregulating not only some of 82 markers of 7 VSMC-plastic cell types, including fibroblast, osteogenic, myofibroblast, macrophage, adipocyte, foam cell, and mesenchymal cell, but also 18 new cell types (out of 79 human cell types with 8065 cell markers); 6) analyses of gene-deficient transcriptomes indicated that antioxidant TF NRF2 suppresses; however, the inflammatory TFs and master regulators AHR, NFkB, NOX2, PERK, and SET7 promote 12 lists of innate immune gene upregulation in atherosclerosis, AAA, and DAMPs-stimulated VSMCs; and 7) both SET7 and trained tolerance-promoting metabolite itaconate contributed to twin-peak upregulation of cytokines in AAA. Our findings have provided novel insights on the roles of innate immune responses and nuclear stresses in the development of AAA, atherosclerosis, and VSMC immunology and provided novel therapeutic targets for treating those significant cardiovascular and cerebrovascular diseases.